Fuelwood characteristics of tree species in homegardens of Kerala, India - A. Shanavas and B. Mohan Kumar (Agroforestry Systems 58: 11-24, 2003., 2003)
Indiscriminate use of natural resources in the past has lead to fuelwood shortages in many parts of the tropical world. To surmount this domestic energy crisis, not only degraded sites must be planted with trees having high fuel value potential, but also agroforestry promoted on arable lands. To enable choice of species for such energy plantations/agroforests in the humid tropics of peninsular India, we assessed the heat of combustion and physical properties that determine combustion of phytofuels, such as ash content, specific gravity and moisture content. Bark and wood samples of 45 multipurpose tree species in the homegardens of Kerala, India and three fuel materials of local importance (coconut [Cocos nucifera] endocarp, dried coconut spathe and dehiscent rubber [Hevea braziliensis] pericarp) were evaluated. Variations abound in the calorific values and physical properties of species and tissue-types. In general, heat of combustion and specific gravity followed the sequence: heartwood > sapwood > bark, while mean ash percentage followed a reverse order (bark > sapwood > heartwood). Ash content had a negative correlation with heat of combustion, but specific gravity exerted a positive influence. Furthermore, ash content and wood specific gravity were inversely related. Although green moisture content increased in the order: bark < heartwood < sapwood, it failed to show any predictable relationship with heat of combustion.